Fully and Partially Integrated Services for Tuberculosis / Human Immunodeficiency Virus in Myanmar : A Health Services Review, Cohort and Molecular Study - Myo Su Kyi (Prince of Songkla University, 2024)
Doctor of Philosophy ( Epidemiology (International Program)), 2019